Proscribing the past or de-proscribing the future: a genealogy and critical discourse analysis of proscription in the North of Ireland, 1887–2017. Issue 2 (3rd April 2019) - Kirkpatrick, Daniel
ABSTRACT: Proscription represents a central pillar of counterterrorism, criminalising organisations and associated practices, and framing proscribed groups as "terrorist". While an emerging field of research on proscription is developing, there has been little attention given to the discursive roots of the practice. Therefore, this article makes three contributions: first, it provides a historical contextualisation of proscription by focusing on the North of Ireland as a crucial case study; second, it provides conceptual depth to existing accounts of proscription through the combination of genealogy and critical discourse analysis; and third, it draws on original and archival material from interviews, parliamentary Hansards, and Government records. Two arguments follow from this analysis: (1) proscription embodies a discourse designed to protect state legitimacy rather than to stop political violence; and (2) the discourse of proscription becomes embedded over time, thereby constraining conflict transformation as material justifications for its continuation become displaced by their symbolism. The article concludes by showing how these arguments have important implications for proscription in international relations, with relevance to a much wider range of cases including Turkey and Sri Lanka.